2018
DOI: 10.1021/acsomega.8b01047
|View full text |Cite
|
Sign up to set email alerts
|

3-Dialkylamino-1,2,4-triazoles via ZnII-Catalyzed Acyl Hydrazide–Dialkylcyanamide Coupling

Abstract: Zinc(II)-catalyzed (10 mol % ZnCl 2 ) coupling of acyl hydrazides and dialkylcyanamides in ethanol leads to 3-dialkylamino-1,2,4-triazoles (76–99%; 17 examples). This reaction represents a novel, straightforward, and high-yielding approach to practically important 3-NR 2 -1,2,4-triazoles, which utilizes commercially available and/or easily generated substrates. Seventeen new 3-NR 2 -1,2,4-triazoles were characterized by HRESI + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…However, Kubota and Uda concluded from 1 H NMR data in CDCl 3 that 3- p -substituted phenyl-5-methylthio-1,2,4-triazoles exist predominantly in form A (position of the NH relative to the SMe substituent) for electron donating substituents ( p -NH 2 , p -OMe) and in form B for substituents with electron withdrawing character ( p -Cl, p -NO 2 ) or when the aromatic substituent was 3-pyridyl. 28 In DMSO- d 6 as solvent, the 1 H NMR spectra of a relatively large series of 3(5)-amino-1,2,4-triazoles containing aryl, 29 heteroaryl 29 a and amidoalkyl 30 substituents consisted of mixtures of isomers A and B , the latter being favoured. It has recently been reported that the three tautomers of a 1,2,4-triazol C-disubstituted with carbamoyl and mercaptoethyl moieties are present in the ratio of 54 : 32 : 14 in the 1 H NMR spectrum measured in DMSO- d 6 .…”
Section: Introductionmentioning
confidence: 99%
“…However, Kubota and Uda concluded from 1 H NMR data in CDCl 3 that 3- p -substituted phenyl-5-methylthio-1,2,4-triazoles exist predominantly in form A (position of the NH relative to the SMe substituent) for electron donating substituents ( p -NH 2 , p -OMe) and in form B for substituents with electron withdrawing character ( p -Cl, p -NO 2 ) or when the aromatic substituent was 3-pyridyl. 28 In DMSO- d 6 as solvent, the 1 H NMR spectra of a relatively large series of 3(5)-amino-1,2,4-triazoles containing aryl, 29 heteroaryl 29 a and amidoalkyl 30 substituents consisted of mixtures of isomers A and B , the latter being favoured. It has recently been reported that the three tautomers of a 1,2,4-triazol C-disubstituted with carbamoyl and mercaptoethyl moieties are present in the ratio of 54 : 32 : 14 in the 1 H NMR spectrum measured in DMSO- d 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The combination of amide and acyl hydrazide is generally referred to as the Pellizzari Reaction (developed in 1894) and can be used to obtain 3,5-diphenyl-1,2,4-triazole at 140 °C [ 11 ]. A recent synthetic example is a procedure based on zinc(II)-catalysed acyl hydrazide-dialkylcyanamide coupling, which allows the utilization of cyanamides bearing donor alkylsubstituents and gives 3-dialkylamino-1,2,4-triazoles such as 3-dimethylamino-5-phenyl-1,2,4-triazole under mild conditions and in high yields [ 12 ]. Another example is the intramolecular ring closure of acyl-amidrazonzes, using tosyl-amidrazone treated with acetyl chloride to obtain 5-methyl-3-(2’,3’,4’,6’-tetra-O-benzoyl-b-D-glucopyranosyl)-1-tosyl-1,2,4-triazole [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…An extensive literature survey revealed that hydrazides have been widely employed in the synthesis of heterocyclic compounds. , With this in mind, we envisaged that a carbohydrazide bearing a semicarbazide (−C­(O)­NHNH 2 ) functional group could be one of the best choices as a reaction partner in coupling with diazo compounds. Currently, the key complication in the synthesis of diazirines is the lack of simple and efficient protocol.…”
mentioning
confidence: 99%